Physical education in transition - Đokić Zoran (University Educons, Faculty of Sports and Tourism, Novi Sad, 2017)
The consequences of physical inactivity and insufficient education about its importance are affecting not only the length and the quality of life, but also the economic aspects, such as health care costs caused by the reduction in labour productivity of the Serbian population. Based on previous experiences of countries in transition and those that have well-arranged systems of education, in terms of teaching of physical education programmes, there are possibilities for the necessary reform of the curriculum, adapted to our abilities and needs. These are primarily related to the objectives of education - proper development and creation of positive habits regarding physical activity and health. So far, the reforms of physical education in Serbia have not produced results. The reform should be the transition from education focused on the program to education focused on the ultimate goals (knowledge, skills, and attitudes towards physical activity, i.e. the lifelong values). The objectives and outcomes of teaching physical education should be individualized according to the psychosomatic status and specific dimensions of that status. Therefore, the role and responsibility of teachers change and it is necessary to reform their education. Of course, government is very involved in all of this, at all levels - throughout strategies and campaigns to raise awareness of the nation and its knowledge about the importance of physical activity through all forms of education.